2007
DOI: 10.1080/15434610600854400
|View full text |Cite
|
Sign up to set email alerts
|

A Reader's Guide to Family Stress Literature

Abstract: This guide introduces the reader to family stress literature, including a variety of topics that are related to family stress: (a) health and family stress, as well as resilience research; (b) physical health issues and family stress; (c) biosocial models and family stress; (d) neighborhood and other community contexts and family stress; and (e) international perspectives on family stress. Next, the guide describes some research trends in response to specific stressors: (a) work and family; (b) family violence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…There is a huge volume of research from different disciplines such as sociology, psychology, and family studies that already carefully attend to family-level stressors, moderators, and/or outcomes (Malia 2007;Patterson 2002). Theories such as Bowen theory (see Klever 2005 for an overview), the ABCX model of family stress (e.g., McCubbin and Patterson 1983;McCubbin et al 1980), family systems theory (e.g., Broderick 1993), the family stress approaches developed by Walker (1985) and by Conger and Elder (1994) and others link closely with some of the positions presented here.…”
Section: The Stress Process Model and Family Stress Researchmentioning
confidence: 99%
“…There is a huge volume of research from different disciplines such as sociology, psychology, and family studies that already carefully attend to family-level stressors, moderators, and/or outcomes (Malia 2007;Patterson 2002). Theories such as Bowen theory (see Klever 2005 for an overview), the ABCX model of family stress (e.g., McCubbin and Patterson 1983;McCubbin et al 1980), family systems theory (e.g., Broderick 1993), the family stress approaches developed by Walker (1985) and by Conger and Elder (1994) and others link closely with some of the positions presented here.…”
Section: The Stress Process Model and Family Stress Researchmentioning
confidence: 99%
“…For example, studies have shown that 23-29 % of mothers screen positive for clinically significant depressive symptoms (Bauer et al 2013;Olson et al 2005) and approximately 6 % meet diagnostic criteria for post-traumatic stress disorder (Chemtob et al 2013). Poor parental mental health negatively affects child wellbeing and family functioning (e.g., Barrett et al 1996;Burke 2003;Chemtob et al 2013;Downey and Coyne 1990;Garber et al 2009;Gershoff et al 2003;Hammen et al 2004;Malia 2007;Patterson and Cobb 1971;Patterson 1982;Riley et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…When the stress is internal to the family as in the case of maternal depression, it may be more difficult for family members to remain connected and feel supported through the challenges they face. Supplementing family stress theory is over 20 years of empirical research on maternal depression (Downey & Coyne, 1990; Goodman & Gotlib, 1999; Lewinsohn et al, 1994; Malia, 2007; Radke-Yarrow, 1998; Timko et al, 2002) that has consistently shown that when a mother is depressed, the family may experience diminished communication, lack of parental warmth, inconsistent discipline, decreased pleasant activities, heightened family stress, and maternal withdrawal, among others. These changes may foster misunderstanding about the mother’s behavior, and resentment, self-blame, and worry.…”
mentioning
confidence: 99%